Differential expression of C5aR1 and C5aR2 in innate and adaptive immune cells located in early skin lesions of bullous pemphigoid patients - Emtenani, Shirin; Holtsche, Maike M.; Stahlkopf, Richard; Seiler, Daniel L.; Burn, Timothy; Liu, Huiqing; Parker, Melissa; Yilmaz, Kaan; Dikmen, Hasan O.; Lang, Markus Huber; Sadik, Christian D.; Karsten, Christian M.; et al. (Frontiers in Immunology, 2022)
Bullous pemphigoid (BP), the by far most frequent autoimmune subepidermal blistering disorder (AIBD), is characterized by the deposition of autoantibodies against BP180 (type XVII collagen; Col17) and BP230 as well as complement components at the dermal-epidermal junction (DEJ). The mechanisms of complement activation in BP patients, including the generation of C5a and regulation of its two cognate C5aRs, i.e., C5aR1 and C5aR2, are incompletely understood. In this study, transcriptome analysis of perilesional and non-lesional skin biopsies of BP patients compared to site-, age-, and sex-matched controls showed an upregulated expression of C5AR1, C5AR2, CR1, and C3AR1 and other complement-associated genes in perilesional BP skin. Of note, increased expressions of C5AR2 and C3AR1 were also observed in non-lesional BP skin. Subsequently, double immunofluorescence (IF) staining revealed T cells and macrophages as the dominant cellular sources of C5aR1 in early lesions of BP patients, while C5aR2 mainly expressed on mast cells and eosinophils. In addition, systemic levels of various complement factors and associated molecules were measured in BP patients and controls. Significantly higher plasma levels of C3a, CD55, and mannose-binding lectin-pathway activity were found in BP patients compared to controls. Finally, the functional relevance of C5aR1 and C5aR2 in BP was explored by two in vitro assays. Specific inhibition of C5aR1, resulted in significantly reduced migration of human neutrophils toward the chemoattractant C5a, whereas stimulation of C5aR2 showed no effect. In contrast, the selective targeting of C5aR1 and/or C5aR2 had no effect on the release of reactive oxygen species (ROS) from Col17-anti-Col17 IgG immune complex-stimulated human leukocytes. Collectively, this study delineates a complex landscape of activated complement receptors, complement factors, and related molecules in early BP skin lesions. Our results corroborate findings in mouse models of pemphigoid diseases that the C5a/C5aR1 axis is pivotal for attracting inflammatory cells to the skin and substantiate our understanding of the C5a/C5aR1 axis in human BP. The broad expression of C5aRs on multiple cell types critical for BP pathogenesis call for clinical studies targeting this axis in BP and other complement-mediated AIBDs.